Cycloaddition versus Alkylation Reactions of 2‐Vinylindoles with α, β‐Unsaturated Carbonyl Compounds Under Gold Catalysis (Eur. J. Org. Chem. 28/2013). Issue 28 (24th September 2013) - Pirovano, Valentina; Dell'Acqua, Monica; Facoetti, Diego; Nava, Donatella; Rizzato, Silvia; Abbiati, Giorgio; Rossi, Elisabetta
Abstract : The cover picture shows two distinctive features discovered during our studies on the Diels–Alder reactions of 2‐vinylindoles with activated carbodienophiles. The scheme shows how the final outcome of the reaction [Diels–Alder (DA) cycloddition versus Michael addition (MA)] is mainly directed by the electronic properties of the reacting diene. The lowering of the nucleophilic character of the indole nitrogen atom with the carbamate substituent prevents the formation of MA compounds and shifts the reaction toward the exclusive formation of DA adducts. The photos mimic two opposed reaction conditions for classical Lewis acid and for gold‐catalysed reactions [BF3 at –20 °C and cationic gold(I) species or gold(III) chloride at room temperature, respectively]. Details are discussed in the article by E. Rossi et al. on p. 6267 ff. The photos are a courtesy of Mr. Gianfranco Caselli; the authors gratefully acknowledge Ms. Susanna Ricci for the graphical design.page 6267 ff.